Shelf life enhancement of low calorie and fiber-enriched Sandesh by Modified Atmosphere Packaging - Rai, Himanshu Kumar; Rai, Dinesh Chandra; Kumar, Arvind; Pandhi, Shikha (Indian Journal of Dairy Science, 2021)
Sandesh is the most popular Chhana-based sweet delicacy of the eastern part of India, especially West Bengal, India. Sandesh is a heat-acid coagulated product that is rich in high quality animal protein, fat, minerals, and vitamins. The present research was conducted to study the effect of three different combinations of gases i.e. 98 % CO2, 98 % N2 and 50 % N2: 50 % CO2 on the shelf life of low calorie and fiber-enriched Sandesh samples. The samples packed under air were kept as control. The samples were stored in a BOD incubator at 25 and 370C and analyzed for microbial, textural and sensorial changes at an interval of 07 days up to 28 days. The samples packed with air showed significantly higher textural and sensorial changes and microbial spoilage as compared to the other three combinations. The results showed that samples packed with 50 % N2: 50 % CO2 combination had better shelf stability as compared to the samples packed under air, 98 % N2 and 98% CO2.